Enhancing strategic planning through strategy instruction: the effect of two types of strategy instruction on learners’ oral planned performance - André Luís Specht; Raquel Carolina Souza Ferraz D'Ely (Ilha do Desterro)
This study aimed at investigating the impact of two types of strategy instruction on Brazilian learners’ planned speech performance at the level of complexity, accuracy, fluency, and adequacy. In order to do so, three groups participated in the present study: (1) the integrated group received strategy instruction during their regular English classes; (2) the isolated group received strategy instruction in a separate course; and (3) the control group received no strategy instruction. The groups also performed two narrative tasks before and after treatment, preceded by 10 minutes of strategic planning. Learners’ oral performance was analyzed and the statistical results showed that (i) the groups that received treatment outperformed the control group; and (ii) the isolated group produced more adequate and accurate speech, while the integrated groups improved their performance in terms of adequacy solely. In conclusion, one can claim that, in spite of the type of treatment, strategic planning can be enhanced by strategy instruction, shedding light on both Language Pedagogy and strategic planning research.